Resting‐state amplitude of low‐frequency fluctuation is associated with suicidal ideation - Lan, Martin J.; Rizk, Mina M.; Pantazatos, Spiro P.; Rubin‐Falcone, Harry; Miller, Jeffrey M.; Sublette, M. Elizabeth; Oquendo, Maria A.; Keilp, John G.; Mann, J. John (Depression and anxiety, 2019)
Background Identifying brain activity patterns that are associated with suicidal ideation (SI) may help to elucidate its pathogenesis and etiology. Suicide poses a significant public health problem, and SI is a risk factor for suicidal behavior. Methods Forty‐one unmedicated adult participants in a major depressive episode (MDE), 26 with SI on the Beck Scale for Suicidal Ideation and 15 without SI, underwent resting‐state functional magnetic resonance imaging scanning. Twenty‐one healthy volunteers (HVs) were scanned for secondary analyses. Whole brain analysis of both amplitude of low‐frequency fluctuations (ALFFs) and fractional ALFF was performed in MDE subjects to identify regions where activity was associated with SI. Results Subjects with SI had greater ALFF than those without SI in two clusters: one in the right hippocampus and one in the thalamus and caudate, bilaterally. Multi‐voxel pattern analysis distinguished between those with and without SI. Post hoc analysis of the mean ALFF in the hippocampus cluster found it to be associated with a delayed recall on the Buschke memory task. Mean ALFF from the significant clusters was not associated with depression severity and did not differ between MDE and HV groups. Discussion These results indicate that SI is associated with altered resting‐state brain activity. The pattern of elevated activity in the hippocampus may be related to how memories are processed.